Electrochemical Techniques in Monitoring of Nervous System Drugs - Choinska, Marta; Hrdlička, Vojtěch; Skopalová, Jana; Šelešovská, Renáta; Kolivoška, Viliam; Navrátil, Tomáš (BEST Servis, 2022)
Drugs of the nervous system (ATC group N) belong generally to the most commonly (mis)used substances worldwide. Their determination and monitoring of these drugs and their metabolites in various body fluids or environmental matrices represent a challenge for analytical chemists. Our research is focused on the application of electrochemical methods in the monitoring of the most frequently prescribed and the newly introduced nervous system drugs of precisely specified structures and/or of defined properties. For toxicological and pharmacokinetic reasons, emphasis has been placed on investigating the reaction mechanisms of their metabolite formation. New or alternative to commonly used electroanalytical methods applicable for monitoring and characterization of target compounds in their pure state, in body fluids, wastewaters, and other environmental matrices, has been developed. To improve the chemometric parameters and sensing characteristics, attention was be paid to the construction of new electrochemical sensors, detectors (e.g. screen-printed, 3D printed), or cells, based on (modified/unmodified) traditional or nontraditional materials, preferably usable at the point-of-care.
Elektrochemické techniky v monitorování léků nervového systému
Keywords: nervous system drugs; active pharmaceutical ingredient; metabolites; electrochemistry; analytical chemistry; electrode materials; modifications; body fluids; biologically active compounds; blood; léky nervového systému; aktivní farmaceutická složka; metabolity; elektrochemie; analytická chemie; materiály elektrod; modifikace; tělní tekutiny; biologicky aktivní sloučeniny; krev